Development of new tissue conditioner using acetyl tributyl citrate and novel hyperbranched polyester to improve viscoelastic stability. Issue 6 (June 2015) - Yang, Tsung-Chieh; Cheng, Kuo-Chung; Huang, Chien-Chi; Lee, Bor-Shiunn
Highlights: A new tissue conditioner was developed. Acetyl tributyl citrate and hyperbranched polyester stabilized the viscoelasticity. Acetyl tributyl citrate and hyperbranched polyester had good biocompatibility. Abstract: Objective: The objective was to develop a new tissue conditioner using acetyl tributyl citrate (ATBC), tributyl citrate (TBC), and a novel hyperbranched polyester (TAH) with long-term stable viscoelasticity. Methods: Plasticizers, i.e., ATBC, TBC, TAH (number-average molecular weight, 1306 g/mol; weight-average molecular weight, 4245 g/mol), butyl phthalyl butyl glycolate (BPBG), dibutyl phthalate (DBP), benzyl benzoate (BB), Shofu Tissue Conditioner II (Shofu), and GC Soft-Liner (GC), in nine combinations (ATBC + TAH, TBC + TAH, ATBC, TBC, BPBG, DBP, BB, Shofu, and GC), with gelation times between 120 and 180 s were used; Shofu and GC were used for comparison. The dynamic viscoelasticity properties, i.e., shear storage modulus ( G ′), shear loss modulus ( G ″), loss tangent (tan δ ), and complex dynamic shear modulus ( G *) were determined at 37 °C, using a rheometer, after immersion in water for 0, 1, 3, 7, 14, and 28 d. The surface hydrophobicity was examined using a static contact angle analyzer, and the biocompatibility was evaluated using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay. Weight changes, solubility, and water absorption were measured using an analytical balance. Results: TAH addition increased the viscoelastic stability; ATBC + TAH was the most stable among the tested groups. TAH decreased the contact angle and increased the water absorption, but decreased the ATBC solubility. The ATBC + TAH group biocompatibility was similar to those of the control group. Significance: The developed ATBC + TAH plasticizer has potential applications as a new tissue conditioner. Its clinical efficacy needs to be evaluated in clinical trials.